Associations of addiction-like eating with personal relative deprivation, compensatory health beliefs, and body mass index from the life history perspective - Haofeng Ling; Bin-Bin Chen; Hengyue Zhang; Hong Mian Yang; Anise M. S. Wu (Journal of Eating Disorders)
Abstract Background The rising global overweight/obesity rate has led to an increase of research attention in one of its antecedents: addiction-like eating (AE). Under the framework of life history (LH) theory, the present study aimed at examining not only the association between AE and body mass index (BMI) but also the effects of LH strategy on AE, via two cognitive mediators (i.e., compensatory health beliefs [CHB] and personal relative deprivation [PRD]). Method A convenience sample of 660 Chinese adults (45.9% males, M age=33.33, SD = 7.62, Range = 19–69 years) was recruited to participate in an anonymous online survey. Results Bivariate correlations revealed significant positive association between AE and BMI (r = 0.12, p < 0.001) and negative association between slow LH strategy and AE (r = − 0.38, p < 0.001). Path analyses revealed both significant direct (β=−0.15, 95%CI [− 0.23, − 0.06]) and indirect effects (via CHB and PRD) of LH strategy on AE (β=−0.06, 95%CI [− 0.10, − 0.03] and β=−0.16, 95%CI [− 0.20, − 0.11]). Additional model testing provided preliminary evidence that AE fully mediated the association between LH strategy and BMI (β=−0.03, 95%CI [− 0.06, − 0.01]). The indirect effect of LH strategy on BMI, via CHB/PRD and AE, serially, was also significant (β=−0.02, 95%CI [− 0.03, − 0.01] and β=−0.04, 95%CI [− 0.06, − 0.02]). Discussion Our study provided additional empirical support regarding the capacity of LH theory to shed light on the mechanisms underlying behavioral addiction. This study was the first of its kind to examine how LH strategy may stimulate resource-related cognitive beliefs, which contribute to addictive behaviors and associated outcomes. Findings have useful implications regarding future research directions and interventions targeting AE and weight control.